Empirical Analysis of the SAC-OCDMA-WDM System by Leveraging the AND Subtraction Technique (AIUB Journal of Science and Engineering (AJSE), 2024)
This study used C-band carrier frequency to assess Spectral Amplitude Coding Optical Code Division Multiple Access or SAC-OCDMA systems using Fiber Bragg Gratings (FBG) as encoders and decoders by implementing the AND subtraction detection technique. The optical transmission distance, optical power, channel bandwidth, data rate, and number of channels are only a few of the many factors that affect how well a system performs. Numerous simulations have been conducted to analyze the influence of the above-mentioned parameters on the system’s performance. The proposed SAC-OCDMA system has been integrated with the Wavelength Division Multiplexing or WDM system to increase the active channel's quantity. The network has been designed and analyzed using commercially available Optisystem software. The proposed SAC-OCDMA system architecture with two channels stays within operational limit up to unrepeated transmission over 336 km at a data rate of 1.6 Gbit/s. These results were attained with the pre-FEC threshold. Further, the SAC-OCDMA system has been simulated up to a maximum of ten channels considering the pre-FEC bit error rate threshold. The obtained results have been compared with recently reported technical articles and found superior in terms of the number of channels and transmission distance. The proposed model obtained a superior data rate of 6.4 Gbps, and a maximum transmission distance of 24 km for 10-channel architecture.
Keywords: SAC-OCDMA; Unique Signature Code; FBG; WDM; Optisystem